Halal food production / Mian N Riaz; Muhammad M Chaudry - Riaz, Mian N.
This text offers wide-ranging coverage of Halal food production, including: the domestic and international Halal food market; Halal food laws and regulations; and a step-by-step guide for food comanies to procedures for obtaining Halal certificates